The Influence of Demography, Hedonism, and Financial Literacy on Consumptive Behavior 0f FEB USK Students - kusumawardani, zahra dyahayu; Amri, Amri (International Journal of Kita Kreatif, 2025)
This study examines the influence of demographic factors, hedonism, and financial literacy on the consumptive behavior of students at the Faculty of Economics and Business, Syiah Kuala University. A total of 108 students were selected using purposive sampling. The research investigates the relationship between consumptive behavior as the dependent variable and demographics, hedonism, and financial literacy as independent variables. The findings indicate that consumptive behavior is significantly influenced by demographic characteristics, hedonistic tendencies, and the level of financial literacy. These results highlight the importance of strengthening students financial knowledge as a means of managing spending behavior. The study suggests that universities can play a crucial role by developing programs and policies aimed at improving financial literacy, thereby supporting students in making more responsible financial decisions. .